Regional and grade-based variations in rice price spreads: An analysis of wholesale and retail pricing dynamics in the Philippines - Diaz, Rowell Agliones (Asian Journal of Agriculture and Rural Development, 2025)
The Philippine rice market, the pillar of Filipino food security, is vital to food safety policy and economic stability. This study investigated price integration and studied price spreads (wholesale-retail price differentials) among rice grades (Special, Premium, Well-Milled, and Regular-Milled) and regions. Based on a quantitative research design and secondary data from Philippine government sources, the research employed descriptive statistics, Pearson correlation, and Analysis of Variance or ANOVA to analyze price spreads, regional differences, and wholesale price-price spread relationships. The results indicated large differences in price spreads among rice grades, with Regular Milled having the largest spreads, reflecting higher markups, and Special the smallest, reflecting its premium status. Regional differences in price spreads were large, particularly for lower grades of rice, which can be attributed to transportation costs and supply chain inefficiencies. A positive correlation between wholesale prices and price spreads for all grades was confirmed, reflecting that higher wholesale prices are associated with higher profit margins. The results highlight the need for targeted interventions, such as supply chain optimization and price management programs, to correct regional differences, improve market efficiency, and ensure consumers' equitable access to affordable rice. Practical implications highlight the need for policies that enhance market integration through infrastructure investment, improve transparency via market information systems, monitor price transmission across grades, and address regional price differences to boost efficiency and ensure equitable access to affordable rice.